ANALISIS POTENSI EKSPOR PRODUK DAMAR KURUNG KHAS GRESIK KE SELURUH NEGARA MENGGUNAKAN TRADE MAP - Raden S.M. Setiaji; Minto Waluyo (JOURNAL SAINS STUDENT RESEARCH, 2024)
Exporting is the process of sending goods abroad for sale, with two main options namely, direct export without third-party intermediaries or indirect export through an export management company (EMC) or piggyback export. EMC, based in the United States, serves as an export department for several manufacturers. Export of piggyback involves joint sales with other manufacturers. HS codes and Trade Map, trade data services, are key in understanding and guiding strategic export decisions. Trade Map analysis on parenthetical resin exports shows America, supported by the United Kingdom and France, as a potential country. With understanding and analytical tools such as Trade Map, the company can increase its opportunities in the global market.